2017
DOI: 10.1098/rspb.2016.2581
|View full text |Cite
|
Sign up to set email alerts
|

How numbers of nesting sea turtles can be overestimated by nearly a factor of two

Abstract: Estimating the absolute number of individuals in populations and their fecundity is central to understanding the ecosystem role of species and their population dynamics as well as allowing informed conservation management for endangered species. Estimates of abundance and fecundity are often difficult to obtain for rare or cryptic species. Yet, in addition, here we show for a charismatic group, sea turtles, that are neither cryptic nor rare and whose nesting is easy to observe, that the traditional approach of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 42 publications
2
76
0
Order By: Relevance
“…As part of long‐term satellite tracking studies in the western Indian Ocean and NE coast of Australia (Esteban, Mortimer, & Hays, ; Hays et al, ; Limpus & Limpus, ; Shimada, Limpus, et al, ), we satellite‐tracked adult sea turtles from their breeding sites to their foraging sites (Table S1 which includes details of make and model of tags). In the central Indian Ocean, we equipped nesting green turtles with satellite tags on the island of Diego Garcia within the Chagos Archipelago.…”
Section: Methodsmentioning
confidence: 99%
“…As part of long‐term satellite tracking studies in the western Indian Ocean and NE coast of Australia (Esteban, Mortimer, & Hays, ; Hays et al, ; Limpus & Limpus, ; Shimada, Limpus, et al, ), we satellite‐tracked adult sea turtles from their breeding sites to their foraging sites (Table S1 which includes details of make and model of tags). In the central Indian Ocean, we equipped nesting green turtles with satellite tags on the island of Diego Garcia within the Chagos Archipelago.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study that tracked 10 green turtles ( Chelonia mydas ) in Diego Garcia, Indian Ocean, showed that their mean clutch frequency was six (Esteban et al. ), and led to the understanding that the population at this locality was about one‐half the size of that estimated from previous studies that patrolled beaches on foot to intercept females when they nested. Using the probabilities obtained in Esteban et al.…”
Section: Defining the Norm (Sample Sizes Of A Few 10s Up To 100)mentioning
confidence: 99%
“…Using the probabilities obtained in Esteban et al. (), we can simulate how the confidence limits on estimates of mean clutch frequency change with sample size. For each sample size (3–40), we ran 1,000 simulations and then determined the standard deviation (SD) of the estimate for mean clutch frequency, which reflects the variation in the estimate of mean clutch frequency that might be recorded with that sample size (Fig.…”
Section: Defining the Norm (Sample Sizes Of A Few 10s Up To 100)mentioning
confidence: 99%
“…, Esteban et al. ). In addition, monitoring nesters includes value added to a monitoring program in that additional biological data can be collected from nesters: body length and size distribution changes, nester recruitment, size at maturity, breeding probability, clutch frequency, and clutch size in relation to nester size and status (i.e., neophyte vs. veteran; Broderick et al.…”
Section: Discussionmentioning
confidence: 98%
“…There is an appreciable accuracy gap by using nesting beach data in general as a population index, and a smaller difference between either source of nesting beach data: observed nesters and nests. The inaccuracy of monitoring nests vs. nesters is minimal in comparison, but both population indices are problematic, and observed nests are marginally worse than nesters, but more sensitive to clutch-frequency bias in sampling (which is important if a monitoring group intends to estimate abundance, e.g., Richards et al 2011, Esteban et al 2017). In addition, monitoring nesters includes value added to a monitoring program in that additional biological data can be collected from nesters: body length and size distribution changes, nester recruitment, size at maturity, breeding probability, clutch frequency, and clutch size in relation to nester size and status (i.e., neophyte vs. veteran; Broderick et al 2003, Stokes et al 2014).…”
Section: Discussionmentioning
confidence: 99%